2019
DOI: 10.2174/1570163815666180828113920
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Flavonoids Against Oral Bacteria of Enterococcus Faecalis ATCC 29212 from Sarang Semut (Myrmecodia pendans) and Its Inhibitor Activity Against Enzyme MurA

Abstract: The aim of this work is to isolate antibacterial compounds from Sarang Semut (Myrmecodia pendans) and to evaluate their antibacterial activity against pathogenic oral bacteria of Enterococcus faecalis ATCC 29212 and inhibitory activity against MurA enzyme. The antibacterial compounds from Sarang Semut were isolated by a bioactivity-guided separation method with various solvents and combination of column chromatography on normal and reverse phases. The compounds with concentrations of 1000 and 5000 ppm were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“… 34 On the other hand, fosfomycin as a control showed the MIC value 62.5 μg/mL and does not have MBC value. 35 It means that fosfomycin just inhibits the bacteria growth but not kill the bacteria. Since compound 2 was found in a published paper, the MIC and MBC values were not reported, the structure will be used as a molecule model as isomer compound of 1 for in silico study.…”
Section: Resultsmentioning
confidence: 99%
“… 34 On the other hand, fosfomycin as a control showed the MIC value 62.5 μg/mL and does not have MBC value. 35 It means that fosfomycin just inhibits the bacteria growth but not kill the bacteria. Since compound 2 was found in a published paper, the MIC and MBC values were not reported, the structure will be used as a molecule model as isomer compound of 1 for in silico study.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that the flavonoid isolate from the ethyl acetate fraction exhibits antibacterial properties against E. faecalis with an MIC of 156 mg/mL and an MBC of 625 mg/mL. 30 Flavonoids contained in the M. pendens fraction are very important to inhibit nucleic acid synthesis (caused by topoisomerase inhibition), cytoplasmic membrane function (membrane permeability and leakage), and inhibition energy metabolism. 6,29 Flavonoids such as rutin inhibit bacterial growth by topoisomerase inhibition, which is important for DNA synthesis; quercetin could reduce bacterial membrane permeability and antibacterial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…They were MurB (UniProt ID: Q830P3), RNA polymerase subunit beta (UniProt ID: Q82Z41), ribosomal subunit 30S (UniProt ID: Q82ZI6), ribosomal subunit 50S (UniProt ID: Q839E6), FsrB (UniProt ID: G8ADN9), and GBAP (UniProt ID: G8ADP0). Meanwhile, the eight ligands considered were M. pendans compounds that were published in previous studies [ 31 , 32 , 33 ]. They were ( 1 ) butein or 2′,3,4,4′-Tetrahydroxychalcone, ( 2 ) biflavonoid, ( 3 ) 3″-methoxy-epicatechin-3- O -epicatechin, ( 4 ) benzoic acid, ( 5 ) dibenzo- p -dioxin-2,8-dicarboxylic acid, ( 6 ) pomolic acid, ( 7 ) betulin, and ( 8 ) β -sitosterol tridecanoil glucopyranose.…”
Section: Methodsmentioning
confidence: 99%
“…Sarang semut, Myrmecodia pendans , is one of the original Indonesian herb plants known to consist of antibacterial compounds [ 26 , 27 , 28 , 29 , 30 ]. There are flavonoids, phenolics, steroids, and terpenoids, which have the ability to inhibit and kill bacteria including E. faecalis, Streptococcus mutans, and Streptococcus sanguinis [ 31 , 32 , 33 , 34 ]. However, their mechanism has not yet been found.…”
Section: Introductionmentioning
confidence: 99%